2018
DOI: 10.1029/2018gl077334
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Response to the Solar Eclipse of 21 August 2017 in Millstone Hill (42N) Observations

Abstract: This study examines the ionospheric changes associated with the solar eclipse of 21 August 2017. The effects associated with the passage of the eclipse shadow were observed more than 1,000 km away from the totality at midlatitudes using the Millstone Hill incoherent scatter radar and digisonde. There was a 30–40% decrease in electron density, a 100‐ to 220‐K decrease in electron temperature, and a 50‐ to 140‐K decrease in ion temperature. Surprisingly, the greatest decrease in electron density occurred above 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 16 publications
(44 reference statements)
8
54
1
Order By: Relevance
“…Perturbations are also seen immediately prior to the start of geomagnetic disturbances (0 UTC on 22 August 2017). These premidnight perturbations might be associated with the aftereffect of the eclipse, as Goncharenko et al () also reported enhanced plasma density over MH around 21 UTC (21 August) based on radar measurements. Goncharenko et al () attributed these enhancements to the eclipse's aftereffect.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Perturbations are also seen immediately prior to the start of geomagnetic disturbances (0 UTC on 22 August 2017). These premidnight perturbations might be associated with the aftereffect of the eclipse, as Goncharenko et al () also reported enhanced plasma density over MH around 21 UTC (21 August) based on radar measurements. Goncharenko et al () attributed these enhancements to the eclipse's aftereffect.…”
Section: Resultsmentioning
confidence: 88%
“…These premidnight perturbations might be associated with the aftereffect of the eclipse, as Goncharenko et al () also reported enhanced plasma density over MH around 21 UTC (21 August) based on radar measurements. Goncharenko et al () attributed these enhancements to the eclipse's aftereffect. On the other hand, the postmidnight DTEC, red and green line brightnesses and MUF dynamics were more likely associated with the TIDs generated due to an increase in auroral currents as a result of enhanced geomagnetic activity.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Millstone Hill experienced a partial eclipse starting at 17:27 UT, maximizing at 18:46 UT at nearly 63% obscuration, and ending at 19:59 UT. The observed response was obtained using 22 August 2017 as the reference day, following Goncharenko et al (2018). The latter three variables are only shown up to 400-km altitude, as results obtained for higher altitudes are considered less reliable, while electron density is shown up to 550 km altitude.…”
Section: Comparison To Observationsmentioning
confidence: 99%
“…Figure 10 shows the response in electron density, electron and ion temperature, and vertical drift as simulated by GITM and as observed by the radar. There are arguments to be made for either of these days to be the most appropriate (see Coster et al, 2017;Goncharenko et al, 2018), so we follow here the methods used by the experts on the data sets in their respective publications. The observed response was obtained using 22 August 2017 as the reference day, following Goncharenko et al (2018).…”
Section: Comparison To Observationsmentioning
confidence: 99%